Pancreatic Enzyme Replacement Therapy in Patients Undergoing First-Line Gemcitabine Plus nab-paclitaxel for Advanced Pancreatic Adenocarcinoma - Trestini, Ilaria; Carbognin, Luisa; Peretti, Umberto; Sperduti, Isabella; Caldart, Alberto; Tregnago, Daniela; Avancini, Alice; Auriemma, Alessandra; Orsi, Giulia; Pilotto, Sara; Frulloni, Luca; Capurso, Gabriele; et al. (Frontiers in Oncology, 2021)
Background: The clinical consequences of pancreatic exocrine insufficiency and its treatment in advanced pancreatic ductal adenocarcinoma (PDAC) are poorly investigated. This retrospective study aims at investigating the pancreatic enzyme replacement therapy (PERT) use and its impact on survival and maldigestion-related symptoms in advanced PDAC patients undergoing chemotherapy. Methods: A retrospective analysis was conducted on advanced PDAC patients, treated with first-line gemcitabine plus nab-paclitaxel at two academic institutions (March 2015-October 2018). Data were correlated with overall survival (OS) using Cox regression model. Kaplan-Meier curves were compared using Log-Rank test. Results: Data from 110 patients were gathered. PERT was administered in 55 patients (50%). No significant differences in baseline characteristics with those who did not receive PERT were found. Median OS for the entire group was 12 months (95% CI 9-15). At multivariate analysis, previous surgical resection of the primary tumor, (HR 2.67, p=0.11), weight gain after 3 months (HR 1.68, p=0.07) and PERT (HR 2.85, p≤0.001) were independent predictors of OS. Patients who received PERT reported an improvement of maldigestion-related symptoms at 3 months more frequently than patients who did not (85.2% vs 14.8%, p≤0.0001). Conclusion: PERT is associated with significantly prolonged survival and maldigestion-related symptoms alleviation in advanced PDAC patients.